ANALISIS PERBANDINGAN HUKUM KONTRAK INDONESIA DAN INGGRIS SERTA KESESUAIANNYA DENGAN PRINSIP - PRINSIP UNIDROIT - Nugrahantono, (2024)
Comparative law is a legal discipline that aims to find similarities and differences and find close relationships between various legal systems. Indonesian contract law and English contract law have similarities. This research analyzes the comparison of Indonesian and English contract law, focusing on the differences and similarities of contract law principles in both countries. In addition, this research also evaluates the comparison between UNIDROIT contract principles with Indonesian and English contract law. The type of research in this legal writing is normative legal research, namely research conducted by examining laws and regulations that apply or are applied to a particular legal problem and using comparative law by comparing laws and legal institutions from one or more countries. . The approach used is normative juridical, which involves the study of legal principles and principles, as well as legal theories and expert opinions. The results show that UNIDROIT principles are recognized and implemented in Indonesian and English contract law, reflecting an attempt to unify the approach to international contract law. Nonetheless, there is room for improvement in both countries' contract law systems that have not been specifically regulated in their respective national laws. To enhance the adaptability and relevance of contract law in Indonesia and the UK and ensure alignment with the principles of international contract law governed by UNIDROIT, several steps are suggested. First, Indonesia may consider revising its contract law foundation, which is currently sourced from the Civil Code, by integrating flexibility elements to more quickly adapt to global contract developments. These steps are expected to strengthen both countries' contract law frameworks and support harmonization with international contract law norms.